Toward the Scientific Defence of Historical Materialism : Basic Elements of the Historical View of Nature, Cognition from the Historical Point of View, The Science of Social Consciousness - Bogdanov, Alexander Aleksandrovich, (Historical Materialism Book Series ;, 2026)
Written under conditions of tsarist censorship, Basic Elements of the Historical View of Nature appears to be a dispassionate account of nature, life, the psyche, and society, based on the most up-to-date science, but, in fact, it has a Marxist goal: to defend the idea of historical materialism. After developing a thoroughly materialist, determinist view of reality, Bogdanov explains how forms of social labour determine the forms of human ideology. Cognition from the Historical Point of View explains the causal connections between labour, forms of cognition, and ideological constructs. Finally, The Science of Social Consciousness , written after the relaxation of censorship, presents a history of European ideological development from an explicitly Marxist point of view.